PEMBANGUNAN WEBSITE ANGKASA PURA - QUICKCONNECT: SISTEM PENCARIAN NOMOR TELEPON OPERASIONAL DI BANDARA INTERNASIONAL I GUSTI NGURAH RAI - Pande Komang Bhargo Anantha Yogiswara; I Gusti Ngurah Anom Cahyadi Putra; I Gusti Agung Gede Arya Kadyanan (Jurusan Informatika, Fakultas Matematika dan Ilmu Pengetahuan Alam, Universitas Udayana, 2026)
The QuickConnect website was developed to enhance operational communication efficiency at I Gusti Ngurah Rai International Airport. This system is designed to provide fast and centralized access to employee contact information across divisions, streamlining phone number searches during urgent situations. This project was conducted as part of a Field Work Practice (PKL) in the Informatics Program at Udayana University, employing methods of needs analysis, planning, development, training, and continuous evaluation. The QuickConnect implementation is anticipated to improve inter-division coordination, reduce contact search time, and elevate the quality of airport operational services. This platform is projected as a potential model digital solution for implementation in similar environments.